Respuesta :

Answer:

2

Step-by-step explanation:

You have to find a number that added with -6 equals -4, and multiplied equals -12.

Just have to do the opperations and that is all!

[tex](x-6)(x+2)=x^2+2x-6x-12=x^2-4x-12[/tex]

Hope you like it!

Answer:

Option C is the answer.

Step-by-step explanation:

Simon is factorizing the polynomial x² - 4x - 12 = (x - 6)( x + ......)

We will factorize the left hand side of the given expression

x² - 4x - 12

= x² - 6x + 2x - 12  

Now we will break 12 into the factors so that sum of the factors should equal to 4

{ 6 × 2 = 12 and 6 - 2 = 4]

= x(x - 6) + 2(x - 6)

= (x + 2)(x - 6)

Therefore, the blank space should be replaced by 2.

Option C is the answer.